2014
DOI: 10.1186/1471-244x-14-156
|View full text |Cite
|
Sign up to set email alerts
|

Mental health related determinants of parenting stress among urban mothers of young children – results from a birth-cohort study in Ghana and Côte d’Ivoire

Abstract: BackgroundThere are limited data on the parenting stress (PS) levels in sub-Saharan African mothers and on the association between ante- and postnatal depression and anxiety on PS.MethodsA longitudinal birth cohort of 577 women from Ghana and Côte d’Ivoire was followed from the 3rd trimester in pregnancy to 2 years postpartum between 2010 and 2013. Depression and anxiety were assessed by the Patient Health Questionnaire depression module (PHQ-9) and the Generalized Anxiety Disorder (GAD-7) at baseline, 3 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 72 publications
2
21
0
Order By: Relevance
“…A higher prevalence of maternal depression was estimated (33.5%) than previously reported for a population of mothers in Ghana (3.8–27.8%) [11, 13, 3236]. Among these studies the highest rate (27.8%) was reported for mothers in Northern Ghana [11] while lower rates were reported for southern Ghana (3.8–11.3%).…”
Section: Discussionmentioning
confidence: 81%
“…A higher prevalence of maternal depression was estimated (33.5%) than previously reported for a population of mothers in Ghana (3.8–27.8%) [11, 13, 3236]. Among these studies the highest rate (27.8%) was reported for mothers in Northern Ghana [11] while lower rates were reported for southern Ghana (3.8–11.3%).…”
Section: Discussionmentioning
confidence: 81%
“…Two previous studies, both of which used the Centre for Epidemiologic Studies Depression Scale, reported about twice our rate in Northern Ghana mothers i.e., 27.8% in 2016 [4] and 33.5% in 2018 [5]. However, six studies conducted on mothers outside northern Ghana recorded lower rates (3.8–11.3%) [611]. The lack of a nationally representative study on the prevalence of depression in Ghana makes judging these figures difficult.…”
Section: Discussionmentioning
confidence: 99%
“…In the developed world, 10 to 16% of all mothers are estimated to experience depression [2] while in Africa, a review based on 35 studies estimated that 18.3% of mothers have depression [3]. In Northern Ghana, the prevalence of depression was estimated in two community-based studies as 27.8% in 2016 [4] and 33.5 in 2018 [5] while six studies conducted on mothers outside northern Ghana recorded lower rates (3.8–11.3%) [611]. Depression is the leading cause of morbidity and mortality worldwide [12].…”
Section: Introductionmentioning
confidence: 99%
“… Misri et al (2010) , in a study with pregnant women prospectively monitored for depression and anxiety during the third trimester and 3 and 6 months postpartum, found that prenatal depression and anxiety directly impact postnatal maternal parenting stress. In a recent longitudinal birth cohort study following sub-Saharan African women from the third trimester in pregnancy to 2 years postnatal and adjusting for confounders, Guo et al (2014) found that prenatal depression was associated with parenting stress, while prenatal anxiety was not. Another study focused on the role of a woman’s own parenting history in postnatal parenting stress.…”
Section: Introductionmentioning
confidence: 99%